Penetration of a woven CFRP laminate by a high velocity steel sphere impacting at velocities of up to 1875 m/s - Hazell, Paul J.; Cowie, Andrew; Kister, Guillaume; Stennett, Christopher; Cooper, G. A. (Elsevier, 2009)
The impact of a woven 6 mm thick CFRP laminate has been subjected to impact by an annealed steel sphere up to velocities of 1875 m/s. It was observed that above a threshold impact energy, the percentage of kinetic energy dissipated by the laminate was constant. Further, the level of damage, as measured by C-Scan and through-thickness microscopy remained roughly constant as the impact energy was increased. However, the size of the hole formed increased. This suggested that the energy transferred to the target in the velocity range of interest became independent of the delamination. Consequently, the main energy transfer mechanism at the high velocities of impact is thought to be due to the cavity expansion and more importantly, the kinetic energy of the particulates.
Keywords: Carbon fibre; energy dissipation; penetration mechanisms; damage